MANAJEMEN ASUHAN KEBIDANAN PERIMENOPAUSE PADA NY “N” DENGAN MENSTRUASI TIDAK TERATUR DI PUSKESMAS KASSI-KASSI KOTA MAKASSAR TAHUN 2021 - Nur Santi; Zelna Yuni Andryani; A. Tihardimanto (Prodi Kebidanan Universitas Islam Negeri Alauddin Makassar, 2022)
Introduction Perimenopause is a transitional period between premenopause and postmenopause. During the period, natural complaints may occur such as irregular menstruation, hot flushes, and sleeping disorders. Women with irregular menstruation are likely to require midwifery care in order to overcome its various negative effects including anxious feeling, fear, which are normal for perimenopausal women before menopause. The main objective of this research was to investigate perimenopause Midwifery Care Management in Mrs.